A direct adverse effect of smoking. (2021) - Kyriakopoulos, Christos; Gogali, Athena; Chronis, Christos; Kostikas, Konstantinos
Abstract: Smoking has been accounted for numerous adverse effects. We report a direct effect of smoking in a 73-year-old patient, a heavy smoker who presented to the emergency department with a 48-h history of productive cough and fever. Chest x-ray and chest CT revealed right lung infiltrates; however, they were not suggestive of the diagnosis, which was established through flexible bronchoscopy. The specific procedure concurrently contributed to the treatment of the patient.